Early developmental changes in the timing of turn-taking: a longitudinal study of mother–infant interaction - Hilbrink, Elma E. (Front Psychol, 2015)
To accomplish a smooth transition in conversation from one speaker to the next, a tight coordination of interaction between speakers is required. Recent studies of adult conversation suggest that this close timing of interaction may well be a universal feature of conversation. In the present paper, we set out to assess the development of this close timing of turns in infancy in vocal exchanges between mothers and infants. Previous research has demonstrated an early sensitivity to timing in interactions (e.g., Murray and Trevarthen, 1985). In contrast, less is known about infants’ abilities to produce turns in a timely manner and existing findings are rather patchy. We conducted a longitudinal study of 12 mother–infant dyads in free-play interactions at the ages of 3, 4, 5, 9, 12, and 18 months. Based on existing work and the predictions made by the Interaction Engine Hypothesis (Levinson, 2006), we expected that infants would begin to develop the temporal properties of turn-taking early in infancy but that their timing of turns would slow down at 12 months, which is around the time when infants start to produce their first words. Findings were consistent with our predictions: infants were relatively fast at timing their turn early in infancy but slowed down toward the end of the first year. Furthermore, the changes observed in infants’ turn-timing skills were not caused by changes in maternal timing, which remained stable across the 3–18 months period. However, the slowing down of turn-timing started somewhat earlier than predicted: at 9 months.